Pengaruh pendidikan gizi kepada ibu terhadap konsumsi makanan dan status gizi anak balita penderita tuberkulosis primer di rawat jalan RSUP Dr. Kariadi Semarang - Tatik Mulyati; Endy Paryanto Prawirohartono; Toto Sudargo (Jurnal Gizi Klinik Indonesia, 2004)
Background: Tuberculosis is an infectious disease that persists as a public health problem in Indonesia. The tuberculosis infected to the under 5-years old-children namely primary tuberculosis, could decrease the children’s immunity eventually causes death, which were 100.000 death rate 75% are children’s. Conditions of children’s health were deeply depending on the quality and quantity of their food consumption. An adequate consumption is needed to increase their nutrition status. To improve the maternal behavior of children’s food consumption, it is necessary to give nutritional education.Objective: The purpose of this study is to examine the effect of nutritional education on the food consumption and nutrition status of the under 5-years old-children that infected by primary tuberculosis.Methods: The research was an experimental research using randomized controlled trial method. The subject was 1 to 5- year(s) old-children those who infected by primary tuberculosis at Unit Rawat Jalan RSUP Dokter Kariadi Semarang. Two groups chosen by randomized got different treatments, i.e. availability and unavailability of nutritional education. Each group was asked to come to Poliklinik Paru Anak every two-week for two months (4 times). The food consumption data was collected by multiple recalls before treatment and after research. The nutrition status was determined by weight per age and weight per height of Z- Score WHO NCHS.Results: The result of this study showed that after the nutritional education issued, the energy consumption average of children has increase 18.18% from necessity and the protein consumption average of children has increase 21.39% from necessity. There was a significant effect of nutritional education on increasing protein consumption of under 5-years old-children that was infected by primary tuberculosis (p<0.05). It was also showed that the Z-Score increasing (weight per age and weight per height) of children in treatment-group was higher than the control-group.Conclusion: Nutritional education has a significant effect on increasing protein consumption of under 5-years old-children that was infected by primary tuberculosis (p<0.05), or there is increasing of protein consumption about 21.39%.